Help-Seeking Within the Context of Patriarchy for Domestic Violence in Urban Uganda - Gardsbane, Diane (Violence against women, 2022)
This study in urban Kampala contributes to a growing evidence base about the complex contexts within which women make decisions about reporting domestic violence. Based on an intersecting theoretical lens of structural violence, power, and the body, findings suggested that women reported to formal structures primarily for severe physical or economic abuse. Women did not report less severe abuse, and often abandoned reporting even severe abuse, because of the overarching structural patriarchy and violence that exists, as well as women’s habitus that includes the embodiment of social norms that sanction reporting. Yet, while overwhelmingly women are discouraged from reporting domestic abuse, there were important signs of change.